Refugees in the COVID-19 - Rubina Grewal; R.L.Koul (Institute of Medico-legal Publications Pvt Ltd, 2021)
COVID-19 brought about most unprecedented public health and socio-economic crisis in our lifetime. Itaffects us all, especially the vulnerable populations, which refugees and migrants often find themselves in.COVID-19 could have even more dire consequences in refugees camps than in general populations.Refugeesand migrants are potentially at increased risk of contracting diseases, including COVID-19, because theytypically live in overcrowded conditions without access to basic sanitation. The ability to access health-careservices in humanitarian settings is usually compromised and exacerbated by shortages of medicines andlack of health-care facilities. Moreover, refugees typically face administrative, financial, legal and languagebarriers to access the health system.Forced migration is at record highs in 2020, with around 70.8 million people around the world being forciblydisplaced. The risk of communicating the novel covid 19 increases in case of the refugees because theycome from the diverse regions of the world which might be facing a higher risk to lives due to the pandemic.Therefore, the health professionals need to be more vigilant.As the COVID-19 situation around the world changes, CDC (Centers for Disease Control and Prevention)is monitoring COVID-19 risk in each destination and making travel recommendations. Travel HealthNotices inform travelers and clinicians about current health issues that impact travelers’ health, like diseaseoutbreaks, special events or gatherings, and natural disasters, in destinations around the world.The sudden outbreak of the pandemic has posed a serious ultimatum to the world of providing propershelter, asylum and healthcare facilities to the refugees. However, public health professionals, communityorganizations as World Health Organization (WHO) and UN High Commissioner for Refugees (UNHCR),resettlement agencies, and healthcare providers can assist refugees arriving in the United States by providingthem with information they need to protect themselves from COVID-19.